Implementation of Regional Government Policy in Distribution of Farmer Fertilizer Assistance - Funna, Muh. Fikri; Niswaty, Risma; Isgunandar, Isgunandar (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
The agricultural sector is the basis of life for the majority of Indonesia's population and it is hoped that the agricultural sector can become a pillar of economic growth. This type of research uses qualitative research which is a way to understand the meaning of a number of individuals or groups of people who are considered to originate from social problems in implementing regional government policies in the distribution of subsidized fertilizer in which there are inhibiting and supporting factors for the distribution of subsidized fertilizer in Pinrang Regency using data triagulation using observation, interviews, and documentation which is a data analysis technique through data condensation, presentation, and drawing conclusions. This is supported by the implementation of aspects of communication, human resources, attitudes, bureaucratic structure, and the existence of supporting factors and inhibiting factors in implementing the subsidized fertilizer distribution policy in Pinrang Regency. The results of this research The implementation of this policy is still not effective because there are still many problems. This is supported by the realization of aspects of communication, human resources, attitudes, bureaucratic structure, and the existence of supporting factors and inhibiting factors in implementing the subsidized fertilizer distribution policy in Pinrang Regency. This proposal can be used as a basis for designing more detailed and in-depth research regarding the implementation of policies for distributing fertilizer assistance to farmers in Pinrang Regency.